Faktor Determinan Minat Kewirausahaan Mahasiswa Akuntansi di Yogyakarta - Erawati, Teguh; Kumala Devi, Cynthia; Listyawati, Reni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The increase in the number of students becoming candidates for employment has led to an increase in unemployment among students. The study aims to test whether there is an influence between entrepreneurship learning, family environment and income expectations on entrepreneurial interests of accounting students. This research population is a student of the accounting study program of public and private colleges in Daerah Istimewa Yogyakarta (DIY). In the study, sampling techniques used purposive samplings with respondents of 123 students as well as data analysis techniques included descriptive analysis, classical assumption tests, and hypothesis tests. Based on the analysis of data from the study, it can be concluded that entrepreneurial learning has a positive influence on entrepreneurship interests of accounting students, the family environment has a positively influenced enterprise interests for accounting student, and income expectations have a positive impact on enterprising interest of accountancy students. The difference with previous research is by adding an entrepreneurial learning variable. The results of this research imply in the field of accounting that enables entrepreneurs to obtain a variety of financial information that is important in running their business.